2022
DOI: 10.1155/2022/7824084
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Ladle Furnace Slag in Mortar under Standard and Accelerated Curing

Abstract: This research preliminarily investigated the suitability of a locally available ladle furnace slag (LFS) as a partial replacement of cement in mortar. The raw material was first characterized to obtain its chemical and physical properties through particle size distribution, X-ray fluorescence (XRF), X-ray diffraction (XRD), and scanning electron microscopy (SEM). Later, the raw LFS was classified into two categories: (i) raw LFS and (ii) sieved (passing through #200 sieve) LFS and incorporated in mortars as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Several studies explored the use of LF slag as a partial addition during self-compacting concrete formation [88][89][90][91][92]. Anastasious et al [90] created self-compacting concrete (SCC) mixtures using LF slag as a filler and steel fibers as reinforcement.…”
Section: -52 Mpamentioning
confidence: 99%
“…Several studies explored the use of LF slag as a partial addition during self-compacting concrete formation [88][89][90][91][92]. Anastasious et al [90] created self-compacting concrete (SCC) mixtures using LF slag as a filler and steel fibers as reinforcement.…”
Section: -52 Mpamentioning
confidence: 99%
“…In recent years, research has attempted to revalue LFS as a suitable raw material for the manufacturing of mortars [46][47][48][49] and, specifically, concrete [30,50,51]. Its addition, after proper stabilization, has proven that it has the ability to partially replace the fine aggregate, while preserving mechanical properties [31,52].…”
Section: Introductionmentioning
confidence: 99%
“…This incorporation of LFS as SCM does not bring significant differences in essential properties such as anchoring capacity and dynamic modulus of elasticity in relation to mortars without slag 6,15 . Even with an increase in the water/binder ratio, these properties can be maintained, with proper choice of batch and dosage of the LFS 16 . However, chemical expansion may still be a cause for concern, as some studies have shown elevated values at 28 days, leading off a search for methods to mitigate the presence of chemical compounds that trigger volumetric instability.…”
Section: Introductionmentioning
confidence: 99%